New Insights into the Role of Zinc Acquisition and Zinc Tolerance in Group A Streptococcal Infection - Ong, Cheryl-lynn Y. (Infect Immun, 2018)
Zinc plays an important role in host innate immune function. However, the innate immune system also utilizes zinc starvation (“nutritional immunity”) to combat infections. Here, we investigate the role of zinc import and export in the protection of Streptococcus pyogenes (group A Streptococcus; GAS), a Gram-positive bacterial pathogen responsible for a wide spectrum of human diseases, against challenge from host innate immune defense. In order to determine the role of GAS zinc import and export during infection, we utilized zinc import (ΔadcA ΔadcAII) and export (ΔczcD) deletion mutants in competition with the wild type in both in vitro and in vivo virulence models. We demonstrate that nutritional immunity is deployed extracellularly, while zinc toxicity is utilized upon phagocytosis of GAS by neutrophils. We also show that lysosomes and azurophilic granules in neutrophils contain zinc stores for use against intracellular pathogens.